Knee pain after intramedullary tibial nailing: its incidence, etiology, and outcome - Court-Brown, C M; Gustilo, T; Shaw, A D (Journal of orthopaedic trauma, 1997)
To establish the incidence and clinical effects of anterior knee pain after intramedullary nailing of the tibia. A retrospective study. The Royal Infirmary of Edinburgh, Scotland. 169 patients who presented with a tibial diaphyseal fracture and were treated by intramedullary nailing. All patients were treated with a reamed Grosse Kempf tibial nail. Anterior knee pain was assessed with an analogue scale and functional outcome was examined using a series of routine daily activities. Anterior knee pain was found in 56.2% of patients. The only distinguishing feature between patients with and without pain was that the patients who had pain were significantly younger. Most patients had mild pain but there was considerable functional impairment with 91.8% of patients experiencing pain on kneeling and 33.7% having pain even at rest. Nail removal resolved or improved the symptoms in almost all cases. Anterior knee pain is a significant complication of intramedullary nailing of the tibia.